Salam-Linked Waqf Futures Contract: An Innovative Sustainable Financing Model for Forest Farmers in East Kalimantan - Zulkarnain Zulkarnain (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to propose product innovations for Sharia Financial Institutions (SFI) in overcoming problems in capital availability, market access, and land limitations for Forest Farmers Groups by transitioning endemic tree species that are more economically valuable and pro-environment, namely Tamanu Trees. The management of waqf land into Tamanu Industrial Forest through the adaptation of the Salam Linked Waqf Futures Contract scheme will be a source of blended finance and a potential source of carbon/CSR funds for the Forest Farmers Group. This paper uses a descriptive qualitative approach based on in-depth interview, literature review and subjective intuitions. This approach aims to be able to do a precise description of primary and secondary data collected through practitioners, academics, regulators, and publications of the East Kalimantan Central Bureau of Statistics, East Kalimantan Forestry Service, Indonesian Law, related books, scientific articles, journals and previous research, online news and DSN MUI fatwa. After using this approach, the futures contract adaptation model is complemented by SWOT identification, so as to review the futures contract adaptation model through four different sides